1967
DOI: 10.3758/bf03330904
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stress on Stroop color-word performance

Abstract: Based on the Hullian proposition that habit and drive combine, the effects of stress on the Stroop Color-Word Test were investigated in 48 college students, under the expectation that stress lVould effect performance differentially, depending upon the nature of the incongruous stimuli. Significant main effects, stress and competition, as well as their interaction, were found.stroop (1935), observing that it takes more time to name colors than to read color llames (Brown, 1915;Lund, 1927;Ligon, 1932), proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 10 publications
3
29
0
Order By: Relevance
“…The interaction, however, was not significant (F < 1.00). The finding that performance was inferior with a briefer exposure duration is congruent with Hochman's (1967Hochman's ( , 1969 data. These results are consistent with a response competition interpretation of Stroop performance, as Ss in the short duration condition presumably have less opportunity to inhibit the dominant response tendency (i.e., reading the word).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The interaction, however, was not significant (F < 1.00). The finding that performance was inferior with a briefer exposure duration is congruent with Hochman's (1967Hochman's ( , 1969 data. These results are consistent with a response competition interpretation of Stroop performance, as Ss in the short duration condition presumably have less opportunity to inhibit the dominant response tendency (i.e., reading the word).…”
Section: Resultssupporting
confidence: 79%
“…This experiment constitutes a partial replication of two recent studies (Hochman, 1967(Hochman, , 1969 which show that Ss perform significantly better with longer exposure times. Furthermore, this investigation provided an opportunity to evaluate the effects of repeated practice with the same set of items on color-word interference.…”
Section: Introductionsupporting
confidence: 53%
“…While the results partially support Hochman's (1967Hochman's ( , 1969) interpretation of the Stroop task as an index of arousal, both the absence of facilitation of performance under low response competition and the fact that elements of the task served as both a source of stress or arousal and of response competition render the implications of these studies somewhat ambiguous.…”
mentioning
confidence: 38%
“…Hochman (1967Hochman ( , 1969 found that high stress resulted in more verbal errors in the high response competition version but failed to fmd that high stress resulted in fewer errors under low response competition relative to performance in the low stress conditions. While the results partially support Hochman's (1967Hochman's ( , 1969) interpretation of the Stroop task as an index of arousal, both the absence of facilitation of performance under low response competition and the fact that elements of the task served as both a source of stress or arousal and of response competition render the implications of these studies somewhat ambiguous.However, the Stroop color-word task is a potentially convenient and useful performance index of arousal or drive. For example, the instructions and procedure employed in the present research took only a few minutes (and closely followed that of Hochman, 1967Hochman, , 1969.…”
mentioning
confidence: 99%
See 1 more Smart Citation